Modelo de suporte à decisão para avaliação da efetivação das ações de alimentação e nutrição a partir do PMAQ - Salerno, Amanda Amaiy Pessoa (2017)
The expansion and qualification of the food and nutrition actions in the Unified Health System (SUS), are extremely important so that the health scenario takes its responsibilities in the challenge of promoting the Food and Nutrition Security of the population. The actions promoted by the Ministry of Health (MH) and developed by the Primary Health Care (PHC) health teams are: promotion of healthy and adequate food, prevention of nutritional diseases and Food and Nutrition Surveillance. To this end, the General Coordination of the Food and Nutrition Policy (CGAN) of the MH has sought the inclusion of quality indicators in the evaluation instruments of the National Program for Improving Access and Quality of Primary Care (PMAQ) that allow the diagostic of its strategic actions for Nutrition Care. However, in practice, the execution of these actions faces some mishaps. In this perspective, the main objective of this dissertation is to develop a decision support model, based on principles of Psychometrics, in order to evaluate the performance of Family Health teams in the implementation of food and nutrition actions of the municipalities who joined the PMAQ in Brazil. This is a cross-sectional population-based study representative of the Family Health teams of the 27 federative states of Brazil, with a sampling unit of 29,778 units. The data comes from the database of the second cycle of External Evaluation of the PMAQ, conducted in 2013. The data was analyzed from the perspective of Psychometrics, in which the model evaluates the Family Health teams in regard of their classification (critical, inadequate, partially inadequate, partially adequate, adequate and potential), by establishing the relevance of the weights by the specialists for each action. The decision support model verified that 37.99% were adequate in the South region and 22.29% received a classification of partially inadequate for the Central-West region, presenting the highest percentages of adequacy and inadequacy respectively, through the establishment of the weights relevance by the specialists for each action. In addition, São Paulo and Minas Gerais were the states of the Southeastern region that presented most adequate Family Health teams; Rio Grande do Sul and Paraná in the South, were also successful; of the North region, Roraima and Pará stood out positively; in the Northeastern region, Maranhão, Piauí, Ceará and Paraíba had the most sucess, with the latter state showing greater success in the implementation of actions; and finally no state in the Central West region exhibited health teams considered adequate compared to the national average. Therefore, the proposal of the decision support model was presented as a potential tool for evaluation processes in PHC, in relation to the work process of health professionals, and can be used as a support tool to predict the nutritional care situation, with regard to whether or not food and nutrition actions were carried out by eSF, according to the normative reference of the National Food and Nutrition Policy (PNAN).